Time after time: why criminals can't quit crime - Atkins, Chris (Atlantic Books, 2023)
British prisoners have to endure the most inhumane and barbaric conditions imaginable, so why do so many of them keep going back? Former inmate and documentary maker Chris Atkins has spent the last six years tracking the fortunes of a dozen repeat offenders to understand why the state fails to keep them out of trouble. Featuring funny, wild and poignant stories, 'Time After Time' exploits Chris's unprecedented access to the criminal underworld to understand why the system actually makes reoffending all but inevitable for ex prisoners